Efficacy of d-dimer level as a prognostic indicator in COVID-19 infection - Reshma S; Letha V; Deepa S; Sankar S (Asian Journal of Medical Sciences, 2024)
Background: Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2, was first reported in China in 2019 and later declared a pandemic. Coagulation abnormalities play the pivotal role in causing most of the symptoms related to COVId-19 infection. As the pathophysiology of COVID-19 is now being understood, it is found that these coagulation abnormalities, especially thrombosis are very well related to the severity of the disease. D-dimer is a potential biomarker for various thrombotic diseases. This study aims to determine the efficacy of D-dimer, Fibrinogen, Prothrombin time (PT), and activated partial thromboplastin time (aPTT) to determine the severity of COVID-19 infection. Aims and Objectives: The objectives of the study are as follows: (1). To determine the efficacy of D-dimer in assessing the severity of the disease in COVID-19 infection. (2). To determine the role of PT, aPTT, and Fibrinogen levels in assessing the severity of COVID-19 Infection. Materials and Methods: The study was conducted among 160 reverse transcription polymerase chain reaction confirmed COVID-19 patients admitted in Government Medical College, Kottayam. The sociodemographic profile and presenting complaints were obtained using a structured format. Blood samples were collected on the day of admission, the 5th day, and 10th day. Samples are tested for levels of D-dimer, Fibrinogen, PT, and aPTT. Based on the clinical outcome, patients were categorized into two groups: Mild group and severe group. Results: The difference between the median D-dimer at admission in the severe group (1339 ng/mL) and the mild group (390 ng/mL) was statistically significant. Area under the receiver operating characteristic (ROC) for D-dimer was 0.774 and cut-off value was found to be 569 μg/mL with a sensitivity of 83.3% and a specificity of 61.2%. The ROC curve analysis, area under the curve of PT also can be used for diagnosis with 76.3% with 76.3% sensitivity and 61.2% of specificity. Conclusion: Coagulopathy is an important complication of COVID-19 patients and is related to severity as well as prognosis of disease. D-dimer and PT can be used as reliable and convenient parameter for assessing coagulopathy and severity in COVID-19 infected patients.